PENGGUNAAN LKPD SEBAGAI MEDIA PENDUKUNG PEMBELAJARAN PJOK DI SMKS PGRI BAJAWA - Maria Wae; Octavianus Marianus Penu; Yohanes Bayo Ola Tapo (Cermat : Jurnal Cendekiawan dan Riset Multidisiplin Akademik Terintegrasi, 2026)
Physical Education, Sports, and Health (PJOK) learning requires active student involvement both physically and mentally. However, in practice, PJOK learning still faces several challenges, such as differences in students’ abilities and the limited use of learning media that can help students understand practical activities systematically. One of the learning media that can be used to support PJOK instruction is the Student Worksheet (LKPD). This study aims to describe the use of LKPD as a supporting medium for PJOK learning at SMKS PGRI Bajawa. This research employed a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation conducted during the Teaching Practice Program (PLP). The research subjects consisted of PJOK teachers and students. The results indicate that the use of LKPD helps teachers manage learning more systematically, increases students’ activeness and involvement in learning activities, and facilitates students’ understanding of PJOK materials. Therefore, LKPD can be considered an effective supporting medium for PJOK learning at SMKS PGRI Bajawa.